Analisis Yuridis Tindak Pidana Pencurian dengan Pemberatan Ditinjau dari Pasal 365 Ayat (1) dan Ayat (2) Ke-2 KUHP : Studi Kasus Putusan No. 751/PID.B/2021/PN JKT.TIM - Januari Sihite; Tubagus Ahmad Suhendar (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
Theft accompanied by other acts such as violence resulting in death, including provisions stipulated in Chapter XXII Book II of the Criminal Code. Theft which resulted in death is regulated in Article 365 paragraph (3) of the Criminal Code. Overall, theft is a crime. A criminal act is a criminal act, which is punishable by imprisonment and/or a fine. Imprisonment is an unpleasant punishment for the recipient (the person receiving it). People who are imprisoned for some time do not enjoy freedom, can breathe outside the prison. One of the objectives of this research is to socialize to the public the crime of theft that is committed by more than one person is the crime of theft by weighting. The method used in this study is to use the literary method, where researchers obtain from library materials such as: books (literature), magazines, newspapers, laws and regulations, general dictionaries, legal dictionaries and encyclopedias and the research results obtained from this writing, it is the judge's consideration, to impose a sentence of 2 (two) years each, to the defendant because based on the witnesses, the evidence available to the defendants is proven guilty. for 2 (two) years in prison because defendants 1, 2, 3 and 4 were proven to have joint intentions.